Perceptions of the Qur’an-Based Ideal Da’i on Social Media: Evidence from Digital Da’wah - Nelsa Erdarisna; Nurullah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study examines social media users’ perceptions of the Qur’an-based standards of an ideal da’i in the context of digital da’wah. The rapid development of information technology has reshaped how the public selects and evaluates da’i on social media. In many cases, da’i are recognized more for delivery style and visual presentation than for scholarly authority, raising concerns about the authenticity of da’wah values rooted in the Qur’an. The study aims to describe the level of understanding and perception within the digital community regarding the Qur’anic standards of an ideal da’i and to analyze tendencies in perceptual differences across demographic backgrounds. The research uses a quantitative approach with descriptive analysis and a One-Way ANOVA to assess perception levels and examine differences by gender, age group, and educational level. The findings show that social media users’ perceptions fall within the moderate category (overall mean = 2.88), indicating a fairly good understanding of Qur’anic values for an ideal da’i. However, these values are not yet fully used as the primary reference when evaluating da’i figures on social media. In addition, significant perceptual differences are found across gender, age, and educational groups, suggesting that demographic characteristics influence how users evaluate the ideal da’i according to Qur’anic da’wah values.